Cognitive neural prosthetics.[article]. - Andersen, Richard A.
The cognitive neural prosthetic (CNP) is a very versatile method for assisting paralized patients and patients with amputations. The CNP records the cognitive state of the subject, rather than signals strictly related to motor execution or sensation. We review a number of high-level cortical signals and their applications for CNPs, including intention, motor imagery, decision making, forward estimation, executive function, attention, learning, and multi-effector planning. CNPs are defined by the cognitive function they extract, not the cortical region from which the signals are recorded. However, some cortical areas may be better than others for particular applications. Signals can also be extracted in parallel from multiple cortical areas using multiple implants, which in many circumstances can increase the range of applications of CNPs. The CNP approach relies on scientific understanding of the neural processes involved in cognition, and many of the decoding algorithms it uses also have parallels to underlying neural circuit function.